Strengthening Digital Knowledge Sharing, Training, and Product Innovation Capability on Organizational Performance in the Bridal Makeup Business Community in Semarang Regency, Indonesia - Herlin Dewi Isnaeni; Abdul Aziz (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of Digital Knowledge Sharing and training on Organizational Performance with Product Innovation Capability as a mediating variable in the HARPI Melati bridal makeup business community in Semarang Regency. The researcher used a quantitative approach, employing a survey, by distributing questionnaires to community members. This study used 71 respondents as the sample and analyzed the data using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method in SmartPLS. The results of the study indicate that Digital Knowledge Sharing has a positive and significant effect on Organizational Performance, thereby improving work effectiveness, coordination, and organizational productivity. In addition, Digital Knowledge Sharing has a significant effect on Product Innovation Capability, meaning that the more active members are in sharing information and experiences, the greater the organization's opportunity to generate product innovation ideas. This study also shows that training has a positive and significant effect on Organizational Performance, as it improves member competency and enhances the quality of organizational services. Training also has a significant effect on Product Innovation Capability, enabling work capability development programs to strengthen members' creativity and innovative abilities. These findings indicate that product innovation has not directly impacted organizational performance because it has not been optimally implemented or generated perceived added value. Furthermore, Product Innovation Capability also failed to mediate the influence of Digital Knowledge Sharing or training on Organizational Performance.